Chitosan film incorporated with Garcinia atroviridis for the packaging of Indian mackerel (Rastrelliger kanagurta) - Nurshahira Binti Khairul Zaman; Nyam Kar Lin; Pui Liew Phing (Ciência e Agrotecnologia)
ABSTRACT Herbs and spices, having antimicrobial effect, can be incorporated into edible films, to extend product shelf life and the reduce the risk of microbial growth on food. The aim of this study is to develop chitosan film incorporated with Garcinia atroviridis, also known as ‘asam gelugur’, ‘asam gelugo’, or ‘asam keping’. The film with different concentrations of Garcinia atroviridis (1 to 5% v/v) with chitosan (1.5% w/v) were investigated for its physical, mechanical and antibacterial properties. With the increase of Garcinia atroviridis extract incorporated, water solubility of the films increases (from 21.17 to 53.61%). Increase of Garcinia atroviridis incorporated into chitosan film also increase the total color difference. Film with higher concentration of Garcinia atroviridis extract produced thicker film compared to the film without extract (from 0.048 to 0.143 mm). The film with 5% (v/v) Garcinia atroviridis possessed low tensile strength (3.28 MPa) and elongation at break (13.90%). Young’s modulus was decreased in value (from 0.72 to 0.24 MPa) as the higher concentration of Garcinia atroviridis extract was added. High Garcinia atroviridis extract (5% v/v) in the chitosan films demonstrated greater inhibitory activity against the bacteria strains (Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus). With the edible film of 5% (v/v) Garcinia atroviridis applied, the Indian mackerel was found to have a longer shelf life (3.5 days) as compared to the control (2.5 days).